SISTEM PENGARSIPAN SURAT BERBASIS WEBSITE DI DINAS LINGKUNGAN HIDUP KABUPATEN SERANG - Waliadi Gunawan; Roza Marmay; Tifani Intan Solihati; Widyawati Widyawati; Diego Febri Alfapin; Indra Gunawan (LPPM Unbaja, 2026)
The Serang Regency Environmental Agency carries out government duties in the environmental sector in accordance with the Regional Medium-Term Development Plan in the Regional Medium Term Development Plan (RPJMD). The high volume of correspondence (incoming and outgoing mail) presents a significant performance challenge. Given that the mail management process—from receipt, creation, storage, and documentation—is still performed manually, a solution is needed. Therefore, a Letter Archive Information System developed using PHP and MySQL is crucial. This system functions to record and track all mail, aiming to simplify the process and save time and effort spent searching for archived data. After implementation, this system successfully helped administrators overcome the difficulties of inputting letter data, which was previously done manually. In conclusion, this letter archive system improved overall work efficiency, made data input more effective and efficient, and achieved high levels of satisfaction from administrators.